Route scheduling of Intrakota bus services: a study on drivers problems toward scheduling efficiency / Suhaila Mohamed Nasib - Mohamed Nasib, Suhaila (1998)
Organization is more than one chart that we always seen in a room or hall. Organization is one mechanism where it shows the chain of command of a company or factory. Good organization enables administration operate smoothly and encourage positive development. It helps achieve company vision through their activities continuously. Organization has one main function, that is to manage human resource.